KANCILAN FLORES (Pachycephala nudigula nudigula): THE ICONIC BIRD OF KELIMUTU NATIONAL PARK, INDONESIA - Fauzi, Ridwan; Kuspriyangga, Aditya; Suarmadi, Fendra; Heri Setianto, Teguh; Serepina Saragih, Grace (Indonesian Journal of Forestry Research, 2022)
Kancilan Flores (Pachycephala nudigula nudigula) is an iconic bird of Kelimutu National Park. The bird has a unique characteristic with the ability to make a wide variety of song. The local people call this bird 'Garugiwa' and also 'burung arwah' or 'spirit bird' because it is small and hard to spot but has a loud chirp. Some literature mentions this bird with different scientific names. This study aimed to identify this bird to rectify this misnaming scientifically and to observes Kancilan Flores behavior, habitat, and population. Kancilan Flores is an attractive fauna for tourists. Therefore, this study also recommended potential birdwatching locations for Kancilan Flores. This study used a transect line and direct observation methods. The results showed that the estimated population size of Kancilan Flores in the Kelimutu National Park was 1,667 individuals with a population size range of 1,245–2,089 individuals. The population density of Kancilan Flores was estimated at 0.53 individuals per hectare. The Kancilan Flores is most commonly found at an altitude of 1,500–1,600 m a.s.l. Recommended areas as bird watching locations for Kancilan Flores, namely the Edelweiss Garden, Perekonde, the lower Arboretum, and the Kancilan Flores middle Arboretum. Therefore, it is necessary to protect the population of Kancilan Flores by strictly prohibiting hunting and destruction of their habitat.